Las voces del ahogo y el desahogo: poesía feminista guatemalteca contemporánea en la obra de Ana María Rodas y Luz Méndez de la Vega - Mehlbauer, Weronika (Romanica Silesiana)
Voices of the Opression and Solace: Contemporary Guatemalan Feminist Poetry in the Works of Ana María Rodas and Luz Méndez de la Vega Guatemala, a country with a long patriarchal history, has always been a place of marginalization for its women. Nowadays, the works of the female writers are still being underestimated and rarely appear next to their male colleagues in the national anthologies. There are two principal aims of the present work. The first one is to analyse the poems of the two most prominent female representatives of the Guatemalan feminist poetry: Ana María Rodas and Luz Méndez de la Vega, in order to reclaim their legitimate place in the canon of the Guatemalan literature. The second one it to expose a difficult situation of the contemporary Guatemalan women, and their literary struggle for the right to have their own voice, to reexpress themselves and to break with the traditional roles imposed by the patriarchal society. Key words: Ana María Rodas, Luz Méndez de la Vega, feminism, Guatemala, poetry.